PHYSICAL AND CORROSION ANALYSIS OF DISSIMILAR METAL WELD OF CARBON STEEL AND AUSTENITIC CARBON STEEL IN MULTIPASS WELD DEPOSIT - JAJULI, MUHAMMAD SYAHMI (Universiti Teknologi PETRONAS, 2017)
Welding in general is a fusion between metals by heating and/or pressure. Dissimilar metal weld is common process in fabrication mainly to reduce cost. Stainless steels (SS) are known for its corrosion resistant properties and adequate mechanical properties. With commissioning environment permitted, dissimilar metal weld of SS with carbon steel (CS) can be done. Unfortunately, stress corrosion cracking (SCC) is a familiar problem in the industries especially pipelines. This project focus on SCC in dissimilar weld metal of austenitic SS and CS in multipass weld deposit. The base material used in this research is type 316 for stainless steel (SS) and type 333 grade 6 for carbon steel (CS). In this process, SMAW process are used along with E308L-16 electrode.